PENGEMBANGAN BUDIDAYA IKAN MELALUI PEMBENTUKAN PAGUYUBAN PETERNAK IKAN TAWAR “KAGUNGAN BUDIARTA” DI DESA LUMBANGSARI BULULAWANG MALANG - Rokhmawati, Dian; Mufida, Muslimatul (Nindikayla Institute, 2022)
Lumbangsari Village, Bululawang district, is one of the villages that promotes the Kampung Tangguh program launched by Forkopimda Malang Raya. RT. 07 RW. II prioritizes food security in the Kampung Tangguh program. Among the activities promoted are vegetable planting by mothers and fish farming by fathers. The fish farming carried out is a type of fresh fish. Although it has been running for some residents, the obstacles they face are not small. In addition, many other residents also want to try to pursue fresh fish farming. In addition to the results consumed by themselves, residents also hope to be able to sell fish products to earn income. Paguyuban Kagungan Budiarta was formed to be a forum for communication, discussing all obstacles and difficulties so that they can be solved together. Paguyuban is also a forum for members to develop and obtain guidance through cooperation with other agencies whose results are for the advancement and economic welfare of the members. Through assistance in the formation of this association, the organizational structure of the association has been arranged with 11 administrators consisting of coaches, chairmen, secretaries, treasurers, empowerment and marketing fields as well as 6 members. Currently, membership is still in the scope of RT. 07, and will be developed to the scope of the village